Ultrastructure of the tegument of Prosorhynchoides arcuatus (Linton, 1900) Bray, 1984 (Trematoda, Bucephalidae) - Simone C Cohen; Anna Kohn; Ortrud M Barth (Memorias do Instituto Oswaldo Cruz, 1996)
The tegument of the adult form of Prosorhynchoides arcuatus (Linton, 1900) (Trematoda, Bucephalidae) from the intestine of Pomatomus saltator (L.) from the Atlantic coast of the State of Rio de Janeiro, Brazil was studied by transmission electron microscopy. The tegument consists of two layers: an external, constituted by a syncytium, containing spines, unicilliated papillae, inclusion bodies and mitochondria and an internal, consisting of a muscular layer and mononucleated tegumental cells.